Geodynamic Processes Monitoring of Subway Infrastructure Using Geodetic and Remote Sensing Methods - Khamit, Nurzhan; Jangulova, Gulnar; Kakimzhanov, Yerkin; Kyrgyzbay, Kudaibergen; Zhumatayev, Serik; Atalykova, Nazym; Kozhaev, Zhenis (Civil Engineering Journal, 2025)
This article examines the development of a methodology for monitoring geodynamic processes during the construction of the Almaty metro using an integrated approach that incorporates geodetic methods, laser scanning, and aerospace technologies. The study aims to enhance the safety of underground structures in the context of complex engineering-geological conditions and high-density urban environments. Monitoring was conducted at the "Saryarka" and "Bauyrzhan Momyshuly" stations, employing underground polygonometry, aerial surveys with unmanned aerial vehicles (DJI Mavic 3 multispectral), laser scanning (Faro Focus 3D X), and finite element numerical modeling (PHASE 2, AutoCAD Civil 3D). The geodetic work covered a 3201-meter section with the installation of 34 benchmarks, ensuring a relative measurement error of no more than 1:30,000. Laser scanning achieved an average point cloud density of 7 mm, enabling the creation of precise 3D tunnel models, identification of deviations from the design axis, and determination of critical stress zones. The study revealed that at a depth of 32.28 m, the maximum vertical stress reached 11.2 MPa, and horizontal stress was 2.7 MPa. At a depth of 19.58 m, the vertical stress reached 10.5 MPa, while the horizontal stress was 2.47 MPa. The maximum concentration of stresses in critical zones reached 20 MPa. The use of UAVs and aerospace technologies facilitated the creation of a highly accurate digital terrain model and the identification of potential deformation zones. The findings confirm the necessity of regular monitoring in dense urban and seismically active areas and demonstrate the potential of integrating modern technologies to improve the precision and efficiency of geodynamic assessments. The proposed methodology can be applied not only to metro construction but also to other underground structures, including mining industry facilities, both in Kazakhstan and internationally.